Homo Tangens, or Man Touching and Tangible - J Mizinska (RUDN journal of Sociology, 2011)
The article is devoted to the analysis of the concept sense of touch, which is considered in all its aspects and dimensions. The author's aim is to determine what is touch in terms of philosophy, what types it has and what traditional functions (i.e. prior to the emergence of virtual reality) each of these functions performed. The conducted research allows the author to make a conclusion about the importance of perceiving the role and significance of man as a homo tangens - man touching and tangible.